Pemberdayaan Masyarakat: Upaya Peningkatan Kompetensi Praktisi Kesehatan dalam Analisis Molekuler untuk Diagnosis dan Penatalaksanaan Penyakit: Indonesia - Andini, Ary; Nugraha, Gilang; Hidayat, Muhammad Taufiq; Prayekti, Endah; Salimi, Syafrina Maulidyatus; Navis, Khiliah; Sari, Widya Novita; Fakurazi, Sharida (UII, 2025)
Molecular analysis has played a pivotal role in diagnosing and managing diseases during pandemics by enabling early outbreak detection and rapid identification of disease causes, leading to prompt treatment. However, there is still a pressing need to enhance the understanding and proficiency of molecular diagnostics in Southeast Asia. Therefore, proactive measures should be taken to improve comprehension through seminars and training programs focused on molecular analysis. The objective is to strengthen the diagnostic and management capabilities of healthcare workers concerning infectious diseases in Southeast Asia, ultimately aiming to enhance the overall health of the population. The target participants include healthcare professionals, medical laboratory technicians, educators, and students. Through collaboration with Universiti Putra Malaysia, two significant events were organized. The International Seminar on Medical Laboratory Technology (ISoMLatech), took place on July 5, 2023, with the theme